Does Erythropoietin regulate TRPC channels in red blood cells? - Danielczok, Jens Gerhard; Freichel, Marc (Cellular physiology and biochemistry, 2017)
Background: Cation channels play an essential role in red blood cells (RBCs) ion homeostasis. One set of ion channels are the transient receptor potential channels of canonical type (TRPC channels). The abundance of these channels in primary erythroblasts, erythroid cell lines and RBCs was associated with an increase in intracellular Ca2+ upon stimulation with Erythropoietin (Epo). In contrast two independent studies on Epo-treated patients revealed diminished basal Ca2+ concentration or reduced phosphatidylserine exposure to the outer membrane leaflet. Methods: To resolve the seemingly conflicting reports we challenged mature human and mouse RBCs of several genotypes with Epo and Prostaglandin E2 (PGE2) and recorded the intracellular Ca2+ content. Next Generation Sequencing was utilised to approach a molecular analysis of reticulocytes. Results/Conclusions: Our results allow concluding that Epo and PGE2 regulation of the Ca2+ homeostasis is distinctly different between murine and human RBCs and that changes in intracellular Ca2+ upon Epo treatment is a primary rather than a compensatory effect. In human RBCs, Epo itself has no effect on Ca2+ fluxes but inhibits the PGE2-induced Ca2+ entry. In murine mature RBCs functional evidence indicates TRPC4/C5 mediated Ca2+ entry activated by Epo whereas PGE2 leads to a TRPC independent Ca2+ entry.